(untitled) (Journal of Nepalese Business Studies, 2025)
This study aims to identify the factors influencing employees’ perceptions of glass ceiling in Pokhara Metropolitan City. The study adopted descriptive and casual comparative research design with a pre-validated 5-point Likert scale questionnaire. The survey questionnaire was distributed online, and data were collected from a sample of 131 respondents using the convenience sampling method. The survey included employees from both the private and government sectors in Pokhara Metropolitan City. Three factors were chosen as independent variables; social factors, organizational factors and personal factors while glass ceiling perceptions of employees was taken as the dependent variable. The findings of the study revealed that social factors and organizational factors were found to have a positive and significant influence on glass ceiling perception while personal factors were statistically insignificant. The study identified social factors as a major contributor to the development of glass ceiling barriers for career advancement, especially within organizational environments. Therefore, organizations in Pokhara Metropolitan City could change their policies and work environment to provide a positive environment for employees’ career progress and minimize the existence of the glass ceiling phenomenon in the future. Future research could incorporate additional factors such as psychological and working environment factors to further explore career advancement in other fields, such as the teaching profession.